The past = Le passé [videorecording (DVD)] - Farhādī, Aṣghar, 1972-; Lahidji, Massoumeh; Muṣaffā, ʻAlī, 1966-; Bejo, Bérénice, 1976-; Rahim, Tahar, 1981-; Burlet, Pauline (Sony Pictures Classics, 2014)
"Following a four year separation, Ahmad (Ali Mosaffa) returns to Paris from Tehran, upon his estranged French wife Marie (Bérénice Bejo)'s request, in order to finalize their divorce procedure so she can marry her new boyfriend Samir (Tahar Rahim). During his tense brief stay, Ahmad discovers the conflicting nature of Marie's relationship with her teenage daughter Lucie (Pauline Burlet). Ahmad's efforts to improve this relationship soon unveil a secret from their past."--Publisher's website.